Pengaruh Media Big Book Terhadap Kemampuan Menyimak Anak Usia 5-6 Tahun di TK Pembina HKBP Tarutung - Sofania Magdalena Siadari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of big books on the listening skills of 5-6 year old children at the Pembina HKBP Tarutung Kindergarten. The research hypothesis was: "the use of big books affects the listening skills of 5-6 year old children (group B) at the Pembina HKBP Tarutung Kindergarten, consisting of 70 students. The research sample was determined using a saturated sampling technique, 35 students as the experimental class and 35 students as the control class. The research method used was a quantitative research method with a quasi-experimental method and a nonequivalent control group design. The instrument used in this study was a questionnaire consisting of 17 items. The research data for the questionnaire was analyzed using the mean difference test formula (N-Gain Score). The mean value for the experimental class was 0.7628, which was in the high category. The mean value for the control class was 0.1569, which was in the low category. From the results of the study, an independent test was then conducted using the t-test and obtained a t-count value = 29.766> t-table (α=0.05; df=68) = 1.995. Thus, it can be concluded that the research hypothesis (Ha) is accepted, namely that the big book media affects the listening skills of 5-6 year old children at the Pembina HKBP Tarutung Kindergarten, and H0 is rejected.